A Production systems study of KGEJ Laboratories, Inc. - Alcaraz, Eunice; Dela Vega, Geraldine S.; Tan, Ketwin May S.; Medina, John Howard D. (College of Engineering, 1993)
KGEJ Laboratories, Incorporated, functions as a subcontractor for its numerous principals and clients. The company offers manufacturing and packaging services with an emphssi on expediency, cost effectiveness, and quality. The nature of their operations dictate that they operate as a job shop. PRoviding services tailored to the individual needs of the principals' and clients' products. As the onest of the project, KGEJ management expresses its intereser in revising their current cost estimation system. The existing cost estimation system is based distribution if the durect labor hour worked, direct materials and some overhead expenditures. IT was specified that the new cost estimation system should utilize the Machine Hour Rate. The Machine Hour Rate is the cost of owning and operating a machine and or work station (non-machine) facility for one hour. Obtaining the Machine Hour Rate requires a comprehensive cost breakdown which is carefully allocated among the individual workstations by means of several allocation factors based on items such as labor hours worked, amount of space occupied, and amount of power required. This level of cost breakdown and allocation greatly increases the effectiveness of the cost estimation. The project was limited by the twoo week time period alloted to it. This narrowed the scope in which the recommended cost estimation system was designed. The project team then deemed it necessary to modify two cost estimation systems currently in use in KGEJ's sister and parent companies. One of these already utilizes machine hour rate. The financial manager of KGEJ Laboratories was able to provide all the raw cost information which had to be classified into several allocable budgets. The level of cost breakdowns necessitated the creation of several forms to aid in the cost classification and allocation. The classified cost budgets could then be allocated by means of several allocation factors recommended by both the project team and KGEJ. The pilot implementation of the recommended cost estimation system included in this report reflects figures used for illustrative purposes only. The actual costs, allocation factors, and facilities classifications being confidential. THe purpose of this project is the setting of foundations for the actual design and implementation of the cost estimation system of KGEJ Laboratories, Inc. is planning to adopt. THis planned cost estimation system will run concurrently with the setting up of engineering standards for their production operations.